2016
DOI: 10.1186/s13104-016-2248-3
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory models of adult patients with type 2 diabetes mellitus from urban centers of central Ethiopia

Abstract: BackgroundType 2 diabetes, which is increasing as a public health problem in the low resource settings of Africa has been associated with the high prevalence of micro-vascular complications and increasing levels of macro-vascular complications. There is evidence from the developed world that understanding patient perceptions of chronic illness is important to design effective strategies for helping patients manage these conditions. This study utilized Kleinman’s model to explore the illness perceptions of type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 26 publications
3
57
0
1
Order By: Relevance
“…The rationale for a chosen minority population was the higher risk of type 2 diabetes when compared to the general population. Two studies mentioned the importance of individualised diabetes education programmes as the reason for including participants from a specific geographical area [26,32]. The rationale for comparing perceptions across countries/cultures was that perceptions of diabetes are embedded in a historical and cultural context.…”
Section: Population Samplesmentioning
confidence: 99%
See 4 more Smart Citations
“…The rationale for a chosen minority population was the higher risk of type 2 diabetes when compared to the general population. Two studies mentioned the importance of individualised diabetes education programmes as the reason for including participants from a specific geographical area [26,32]. The rationale for comparing perceptions across countries/cultures was that perceptions of diabetes are embedded in a historical and cultural context.…”
Section: Population Samplesmentioning
confidence: 99%
“…Eleven studies investigated patients' perceptions of identity of type 2 diabetes [14,16,17,23,25,26,[32][33][34][35][36]. The patients in three of the studies reported experiencing symptoms such as fatigue, weight loss, increased thirst and vision problems [14,23,32]. In one study, patients believed that the need for insulin is a symptom of type 2 diabetes [17].…”
Section: Identitymentioning
confidence: 99%
See 3 more Smart Citations